Cable Cage - 03 - (Author); (Interviewer); (Publisher)
Photograph - Cable cage, Athabasca, Alberta. A note on the back reads: This is the cage they used across the river this fall. Had a different engine than last year and it worked well. Carried four passengers and Jeff Coke the operator. Was running over a month and carried as high as 150 passengers a day